PROBLEM-BASED LEARNING WITH VIDEO ANALYSIS: THE CASE OF THE VARIABLE-MASS ATWOOD MACHINE. - J. L. SAQUINAULA-BRITO; J. J. PLAZA-SANTILLÁN; J. D. ORTIZ-MATA; E. A. LAMILLA-RUBIO (Revista Cubana de Física, 2025)
This study applies Problem-Based Learning (PBL) to teaching advanced mechanics in undergraduate physics, focusing on variable mass systems through the Atwood machine with chains. Using the Hmelo-Silver PBL model, a structured sequence guided students in problem analysis, hypothesis generation, self-directed study, experimentation, and reflection. The case study combined Newtonian and Lagrangian modeling with experimental validation via Tracker video analysis, enabling students to connect theoretical derivations with accessible empirical data. Results showed strong consistency between theoretical predictions and experimental measurements, despite minor discrepancies from chain oscillations, link impacts, and video resolution limitations. The approach demonstrated how low-cost tools can effectively support experimental inquiry in physics education. Beyond content knowledge, PBL fostered research-oriented skills such as autonomous planning, problem-solving, and collaborative inquiry. The proposed framework provides a replicable model for integrating abstract theory with experimental practice, strengthening active learning and advancing the role of inquiry-based methodologies in STEM curricula.